THE SYMPTOM AS FORMALIZING SOCIAL BOND. INTERSECTIONS BETWEEN PSYCHOANALYSIS AND POLITICAL. (THE PIQUETEROS) - Fair, Hernán (2013)
The article approaches the symptom like a way of communitarian social bow from a discursive approach with axis in the intersection between lacanian psychoanalysis and theory/political sociology. Placing the axis in the characteristics that the speech of the movement of piqueteros assumes, it maintains that it represents a social symptom that will emerge from the entrails of the menemist equivalencial chain. As well, it indicates that this symptom will manage to conform a new imaginary configuration of social bow from the universal demand by work and social inclusion.